Analisis Nilai Tambah, SaluranPemasaran dan SistemManajemenRantaiPasok di CV Gaharu Plaza Indonesia Pekanbaru - Quan Paulus Giovan; Farida Hanum Hamzah; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
CV Gaharu Plaza Indonesia is one of the few companies that processes agarwood in the Riau province. Poor marketing systems causes the product to be unable to compete in the market. The purpose of this research is to identify and analyse the supply chain management system of agro-industry and efficient marketing channels at CV Gaharu Plaza Indonesia. This research was observed using descriptive quantitative and qualitative analysis methods. Qualitative descriptive analysis is used to analyse the mechanism of supply chains. Descriptive quantitative is used for measuring added value and marketing efficiency. Marketing efficiency can be determined by calculating marketing margin, farmer’s share and marketing efficiency. The value added of the actors are as follows: agarwood farmer (86%), CV Gaharu Plaza Indonesia (88%) and distributor (25%). Agarwood tea’s marketing consist of 3 channels, channel 2 is the efficient channel consisting of marketing margin IDR 7000, farmer’s share 65% and marketing efficiency 8%. Keywords: agarwood tea, supply chain, Hayami method, farmer’s share, marketing efficiency